Serum prolidase activity, total oxidant/antioxidant, and nitric oxide levels in patients with esophageal squamous cell carcinoma - Sayır, Fuat (Turk Gogus Kalp Damar Cerrahisi Derg, 2019)
BACKGROUND: This study aims to assess the prolidase activity, nitric oxide levels, and oxidative status in patients with esophageal squamous cell carcinoma. METHODS: The study included 30 patients with esophageal squamous cell carcinoma (11 males, 19 females; mean age 61±3 years; range, 28 to 77 years) and 30 healthy controls (10 males, 20 females; mean age 58±5 years; range, 31 to 73 years). Serum prolidase activity, total antioxidant capacity, total oxidant status, and nitric oxide levels were measured. In addition, the oxidative stress index was calculated. RESULTS: Prominently elevated serum prolidase activity, oxidative stress index values, total oxidant status, and nitric oxide levels were detected in the patient group (p<0.05). Lower total antioxidant capacity levels were observed in the patient group (p<0.05). CONCLUSION: Increased oxidant status with increased nitric oxide levels and prolidase activity were found in esophageal squamous cell carcinoma patients. Impairment of antioxidant mechanism with increased prolidase activity and nitric oxide levels may have a crucial role in the etiopathogenesis of esophageal squamous cell carcinoma.